PENGARUH MENDENGARKAN MUROTTAL AL-QUR’AN TERHADAP MEMORI KERJA - Istiqomah Nur Aziza; Nanang Wiyono; Afia Fitriani (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2019)
It is important to optimize working memory because it transforms, synergizes and constantly updates new and old information. One way to optimize working memory is to listen to Murottal Al-Qur'an, because it has a harmonious tone which can stabilize the mind to properly process the information. This study aims to determine the effect of listening to the Al-Quran murottal on working memory. The research subjects were 24 students of Psikologi 2017, grouped equally in the control and experimental groups. An experimental intervention was administered for 15 consecutive days lasting 15 minutes and 52 seconds. Measurements in working memory use Operation Span Task, Reading Span Task and Symmetry Span Task. The design of the study used a pre-test post-test control group and the data were analyzed by t-test. The results showed a significant difference between the control group and the experimental group on the symmetry span task subtest (p = 0.044, p <0.05).